Perbandingan Sistem Pendidikan: Sistem Pendidikan Indonesia Dan Malaysia - Kurniawan, Julius Tito; Dompak, Timbul (LPPM Universitas Putera Batam, 2024)
a conversation where we contrast or compare education systems. This publication compares and contrasts the education systems of Malaysia and Indonesia. This study uses the literature technique, where information is gathered from books, journals, and other sources related to the topic to be discussed. The purpose of this discussion is to gain more understanding and information about the education systems in Malaysia and Indonesia. The author produces or obtains conclusions regarding 1) The education system in Indonesia and Malaysia based on the information in the learning materials. 2) The purpose of education in Malaysia and Indonesia. 3) Curriculum in Malaysia and Indonesia. 4) Education policies in Malaysia and Indonesia. 5) Analysis of education in Malaysia and Indonesia.